Link between epigenetic diversity and invasive status of south-eastern European populations of phytopathogenic fungus Cryphonectria parasitica - Vuković, Rosemary; Liber, Zlatko; Ježić, Marin; Sotirovski, Kiril; Ćurković-Perica, Mirna (Environmental microbiology, 2019)
Epigenetic modifications may play an important role in invasion and adaptation of clonal and invasive populations to different environments. The aim of this study was to analyse epigenetic diversity and structure within and among populations of invasive pathogenic fungus Cryphonectria parasitica from south-eastern Europe, where one haplotype S12 dominates. The highest level of epigenetic diversity was found in haplotype S1, followed by S2, while the lowest level of epigenetic diversity was found in haplotype S12. Similar pattern of epigenetic diversity was detected in the control, genetically diverse Croatian population where S1 haplotype dominates. In four south-eastern European populations, the highest level of epigenetic diversity was observed in the Italian population, the oldest population in the studied area, while the lowest diversity was found in most recently established Bulgarian population. This relationship between epigenetic diversity and population age implies the important role of epigenetic modifications on the process of invasion. Our data suggest that epigenetic differences might affect the success of expansion of certain haplotype into new regions. Understanding the role of epigenetic processes in expansion and (pre)adaptation of fungal plant pathogens, besides fundamental knowledge, can contribute to development of strategies for control of fungal spread and pathogenesis.
Keywords: Adaptation, Cryphonectria parasitica, chestnut blight, epigenetics, invasive fungus